Optimal Incentive Contracts when Workers envy their Boss - Robert Dur; Amihai Glazer (Tinbergen Institute, 2004)
A worker's utility may increase with his income, but envy can make his utility decline with his employer's income. This article uses a principal-agent model to study profit-maximizing contracts when a worker envies his employer. Envy tightens the worker's participation constraint and so calls for higher pay and/or a softer effort requirement. Moreover, a firm with an envious worker can benefit from profit sharing, even when the worker's effort is fully contractible. We discuss several applications of our theoretical work: envy can explain why a lower-level worker is awarded stock options, why incentive pay is lower in nonprofit organizations, and how governmental production of a good can be cheaper than private production.
Keywords: D23; J31; J33; M52; 330; Principal-agent; Envy; Compensation; Contracts; Profit-sharing; Stock options; Public vs. private production; Anreizvertrag; Prinzipal-Agent-Theorie; Moral Hazard; Neid